Output hysteresis and optimal monetary policy - Vaishali Garga; Sanjay R. Singh (Federal Reserve Bank of Boston, 2019)
We analyze the implications for monetary policy when deficient aggregate demand can cause a permanent loss in potential output, a phenomenon we term output hysteresis. In the model, the incomplete stabilization of a temporary shortfall in demand reduces the return to innovation, thus reducing total factor productivity growth and generating a permanent loss in output. Using a purely quadratic approximation to welfare under endogenous growth, we derive normative implications for monetary policy. Away from the zero lower bound (ZLB), optimal commitment policy sets interest rates to eliminate output hysteresis. A strict inflation targeting rule implements the optimal policy. However, when the nominal interest rate is constrained at the ZLB, strict inflation targeting is suboptimal and admits output hysteresis. A new policy rule that targets output hysteresis returns output to its pre-shock trend and approximates the welfare gains under optimal commitment policy. A central bank that is unable to commit to future policy actions suffers from hysteresis bias, as the bank's inconsistent policy does not offset past losses in potential output.
Keywords: E52; E61; O41; 330; endogenous growth; zero lower bound; output hysteresis; optimal monetarypolicy